Caracterização de modelos de negócios sob a lógica das estratégias de governança aplicada a produtores de carne bovina - Oliveira, Hugo Moreira de (2017)
Farming has been taking the main position within Brazilian economy, and beef cattle breeding has a very important role to this fact, once the country is the second largest beef producer and exporter in the world. This work is positioned in the field of study of Strategic Management of Industrial Business, searching for the development and competitiveness of these organizations, and it has the purpose of distinguishing different business models to beef producers, adding the logic of the governance structure, whose target is improving this analysis the purpose of distinguishing different business models to beef producers, adding the elements of Governance structures. This descriptive and qualitative research uses the basis from multiple case studies and selects five cases with different beef production models. To collect the necessary data, this work has used semi-structured interviews, documentary analysis and direct observation. The collected data has been analysed from content analysis. To help within this process, the software NVivo has been used as an auxiliary tool in order to treat the data. Considering the theoretical foundation, it has identified six elements that characterize a business model. From the Transaction Cost Economics (TCE) perspective, a seventh element has also been added: the governance structure. These seven elements were represented in a graphical model, with circular shape and divided in four layers. The analysed cases have shown a huge heterogeneity of governance structures, once none of them adopts one single line to be followed in all their operations. Each kind of element adopts a different governance structure. Therefore, it is possible to conclude that each organization has the elements of its business model being controlled by specific governance structures, that are capable of adaptation before the possibilities and necessities of each situation. It is believed that this work has allowed advances in the beef cattle breeding, besides showing potential variables related to the governance structure, what has made the formulation of five propositions. This research has, as its limitation, the low quantity of analysed elements and the absence of qualitative indicators that could allow measuring the collected data. Future studies could improve this perception with more analysed elements, besides the utilization of quantitative methods, the comprehensiveness of cases of chicken and pork producers and also verification of the propositions formulated.